Numerical methods problem solving optimal of technical systems - Климова, А.С. (Proceedings of National Aviation University (archive), 2006)
There are offered some numeral methods of functions eхstremum search for the multicriterial optimization tasks decision. The researches, using experience and possibilities results at the compound technical system optimum planning are presented.